2023
DOI: 10.3390/socsci12010048
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Beliefs and Ontologization of Mothers: A Moderated Mediation Analysis

Abstract: This study combines insights from gender studies and studies on dehumanization to show how gender role beliefs influence attitudes and the attribution of ontologization traits to mothers. A convenience sample of 194 Italian participants read one of three vignettes describing a mother (a heterosexual biological mother, a heterosexual stepmother, or a lesbian stepmother) and her five-year-old son during a moment of disagreement. Participants assessed the depicted mother’s competence and attributed ontologization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, participants did not represent the Portuguese population and generalization of the results is limited. Most participants were mothers, and their expectancies and attitudes facing motherhood, which were not measured, could influence the personal perceptions of changes and, consequently, the mediation model [30]. Also, at-risk families were not frequent or other specific groups such as single mothers and parenting dimensions such as coparenting can differ according to diverse family structures [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants did not represent the Portuguese population and generalization of the results is limited. Most participants were mothers, and their expectancies and attitudes facing motherhood, which were not measured, could influence the personal perceptions of changes and, consequently, the mediation model [30]. Also, at-risk families were not frequent or other specific groups such as single mothers and parenting dimensions such as coparenting can differ according to diverse family structures [31].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as family research scholars have shown, an intensive parenting culture can affect couples' work-care arrange-ments (Faircloth 2021a(Faircloth , 2021bTwamley et al 2021). Moreover, scholars have explored the ontologization of the mother figure (Di Battista 2023). These authors have pointed to the different perceptions of biological mothers, lesbian co-mothers, and step-mothers.…”
Section: Discussionmentioning
confidence: 99%